Dietary and lifestyle inflammation scores in relation to colon cancer recurrence in subgroups of patients based on common molecular tumour characteristics - E. Wesselink; D.E. Kok; K.C. Smit; A.-S. van Lanen; J.W.G. Derksen; M. Koopman; M. Ligtenberg; I.D. Nagtegaal; P.D.M. Rombout; J.H.W. de Wilt; E. Kampman; A.M. May; et al. (ESMO Gastrointestinal Oncology, 2025)
Background: The aim of this study was to investigate associations between the inflammatory potential of diet and lifestyle in relation to colon cancer recurrence in subgroups of patients based on molecular tumour characteristics that also influence the inflammatory tumour microenvironment. Patients and methods: A nested case-control study was implemented in two prospective cohort studies of colon cancer patients. Participants who developed a recurrence were included as cases (n = 167). Matched controls (n = 668) were selected based on incidence density sampling. Lifestyle factors were assessed at diagnosis using self-administered questionnaires and dietary intake was assessed using a food frequency questionnaire. The dietary inflammation score (DIS) and the lifestyle inflammation score (LIS) were constructed. High-throughput next-generation sequencing of tumour tissue was used for mutation and microsatellite instability (MSI) analysis. Associations between the DIS and LIS and recurrence were assessed with conditional logistic regression analyses in all patients, as well as in subgroups based on MSI. For patients with microsatellite stable (MSS) tumours, further stratification based on mutation status of KRAS, BRAF, PIK3CA, TP53 and APC was performed. Results: A more pro-inflammatory diet was not associated with risk of recurrence [incidence rate ratio (IRR) 1.04, 95% confidence interval (CI) 0.96-1.12]. Persons who have a more pro-inflammatory lifestyle may have an increased recurrence risk (IRR 1.21, 95% CI 0.97-1.52), which was most pronounced for persons with MSS and KRAS or PIK3CA wildtype tumours (IRR 1.31, 95% CI 0.90-1.90 and IRR 1.30, 95% CI 0.98-1.71, respectively). Conclusion: Our results suggest that associations between the LIS and recurrence might differ based on molecular tumour characteristics.